Bubble coalescence effects on the geochemical and physical fluctuations of intermediate magmas. Erebus volcano lava lake study case, Antarctica (2018)
Mount Erebus is a stratovolcano at 3794 masl with an approximate volume of 1670 km³ that overlies very thin continental crust (about 20 km width) at Terror Rift, at the Western boundary of the Western Antarctic Rift (Behrendt, 1999). Its main composition is characterized by interbedded pyroclastic phonolites, bomb deposits y lavic flows surrounding a volcanic summit cone in which bottom lies a phonolitic lava lake. On the other hand, the lava lake is characterized by a convective flow and a permanent cyclic degassing. Such cyclicity stands out due as it consititutes changes in the mean level of the lava lake and the geochemical variation of the emitted gases throughout the surface (Molina et al, 2015). Additionally, these cycles are in phase with variations in the gas flux, temperature and velocity that shows off the lava lake surface (Jones et al. 2015; Oppenheimer et al, 2009; Alleti et al., 2004; Peters et al., 2014 a,b). The modeling of a physical phenomenon such as the magmatic ascent is a complex problem even when relatively simple considerations are established. As a consequence, this research work pretends to introduce the process of coalescence to the model proposed by Molina et al (2015). Specifically, the physical approach here proposed is similar to the ones made by Castro et al (2012), and Burgisser and Gardner (2008) through the introduction of three coalescence mechanisms for the volatiles bubbles inside the magma. At the same time, this process allows to modify other physical parameters of the magma such as the effective dynamic viscosity and the magma ascent velocity, in the model proposed by Molina et al (2015). The development of this research work is of great importance as bubble coalescence inside the magma allows to understand better the degassing phenomenon and is useful in later studies of other eruptive regimes and compositional systems.